Pengaruh CAR, NPF, FDR Terhadap Profitabilitas Bank Umum Syariah di Indonesia Dengan Pembiayaan Sebagai Variabel Mediasi - Ulfatul Khasanah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study is to determine the financing ability to mediate CAR, NPF and FDR on the Profitability of Sharia Commercial Banks in Indonesia. This study used a quantitative approach with secondary data types. The sample of this study is a sharia commercial bank registered with OJK for the period 2016 to 2020. By using purposive sampling, 9 Islamic banks were obtained. This study used PLS-SEM analysis. The results showed that CAR, NPF and FDR had a positive effect on profitability. While financing has no effect on profitability. This has an impact on the financing ability to mediate CAR, NPF and FDR. These three variables have not been able to be mediated by financing to profitability.